2010
DOI: 10.1021/ja105194s
|View full text |Cite
|
Sign up to set email alerts
|

Controlled and Chemoselective Reduction of Secondary Amides

Abstract: This communication describes a metal-free methodology involving an efficient and controlled reduction of secondary amides to imines, aldehydes, and amines in good to excellent yields under ambient pressure and temperature. The process includes a chemoselective activation of a secondary amide with triflic anhydride in the presence of 2-fluoropyridine. The electrophilic activated amide can then be reduced to the corresponding iminium using triethylsilane, a cheap, rather inert, and commercially available reagent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
123
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 257 publications
(127 citation statements)
references
References 60 publications
(22 reference statements)
4
123
0
Order By: Relevance
“…9, 169.4, 151.6, 135.4, 131.5, 128.1, 126.5, 123.6, 21.0. It is in good agreement with the reported data [10].…”
Section: Methodssupporting
confidence: 93%
See 1 more Smart Citation
“…9, 169.4, 151.6, 135.4, 131.5, 128.1, 126.5, 123.6, 21.0. It is in good agreement with the reported data [10].…”
Section: Methodssupporting
confidence: 93%
“…However, the conversion was improved from 6.4% up to only 21.1% with residence time increasing from 5 min to 30 min (Table 1). One undesired product, which was assigned to be the O-acetylsalicylaldehyde (3) [10], was yielded within significant quantities. The compound 3 indicated that the process of this reaction could contain O-acetylation.…”
Section: Resultsmentioning
confidence: 99%
“…Compounds 16,19, and 33 offered 66% protection. Compounds 8,9,10,12,13,15,16,17,19,20,25,26,27,28,30,32,33, and 35 showed moderate protective effect in the MES and compounds 11, 18, and 31 were found to be 100% protective. Majority of the compounds, except 22,23,24,29,34, and 36, were active in MES tests making them useful for a broad spectrum of seizure types.…”
Section: Pharmacologymentioning
confidence: 97%
“…Target key intermediate 7 was accomplished by deprotection of Boc group from compound 6 with dioxane in HCl and followed by basification with sodium carbonate solution [24]. The aim of the 7 was introduced to respective sulfonyl chlorides/acid chlorides at the Nposition of triazaspiro bicyclic moiety to lead to the desired compounds 8-37 for structure-activity relationship (SAR) study [25,26]. This was furnished by normal condensation reaction with good yield.…”
Section: Chemistrymentioning
confidence: 99%
“…With the approach of Pelletier (Scheme 32.28), all three classes can be accessed with the same method depending solely on the reaction conditions. 65 Because of their high stability, amides still pose quite a challenge for reduction. Generally, strong reducing agents like aluminum or boron hydrides are inevitable.…”
Section: Reduction Of Secondary Amidesmentioning
confidence: 99%